Potensi Limbah Abu Layang (Coal Fly Ash) Sebagai Koagulan Cair Dalam Pengolahan Air Gambut - Yonda Safutra; Bintal Amin; Sofia Anita (Universitas Riau, 2017)
Coal Fly Ash is waste of coal combustion which is included in toxic and hazardous material (B3). This study aims to find the optimum conditions of liquid coagulant manufacturing process from coal fly ash. The process of making liquid coagulant from coal fly ash is a modification of Park method (1997) to make coagulant from clay, because it has the same composition. The optimum conditions were obtained at 2500C, 60 minutes, 1: 5 ratio and 2M H2SO4 concentration. Furthermore, liquid coagulant at optimum condition was carried out effectiveness test in peat water treatment, the research was done by using randomized complete factorial design (RAL) with 9 treatment combinations and 3 replications, analyzed in the laboratory and analyzed of variance (ANOVA). Parameters measured were color, pH, turbidity, TDS, TSS. The results showed that the difference of coagulant dosage gave significant effect on color, pH, TDS, and turbidity parameters, but no significant effect on TSS parameter. The difference of stirring time significant effect on pH and turbidity parameter while for color, TDS, and TSS parameter no significant effect.